Harnessing advanced extraction and profiling technologies for sustainable phytomolecule-based pest management - Komala, G; Shanthi , Mookiah; Murugan , Marimuthu; KSujay Anand , GK; Vellaikumar , Sampathrajan; Preetha , Gnanadhas; Kavitha, Govindasamy; Madesh, K (Plant Science Today, 2025)
For decades, pest control has primarily relied on the use of synthetic chemicals. Although effective, this method has led to serious issues such as environmental pollution, prompting resistance in pests and posing health risks to beneficial organisms and even humans. Traditional methods used to extract plant-based compounds, such as maceration, Soxhlet extraction and hydrodistillation, are often outdated and inefficient, requiring large volumes of solvents and subjecting sensitive compounds to damaging heat. These ongoing challenges underscore the urgent need to seek safer, more sustainable solutions not only for managing pests but also for obtaining natural bioactive compounds. These methods are associated with high solvent consumption, poor selectivity, thermal degradation of heat-sensitive compounds and low recovery rates of active constituents, which limit the full potential of plant-derived bioactive compounds in pest management. Advanced extraction technologies are increasingly being adopted to overcome these challenges. Techniques such as ultrasound-assisted extraction, microwave-assisted extraction, supercritical fluid extraction and pressurized liquid extraction employ innovative physical principles that enhance mass transfer, protect thermally sensitive bioactives and significantly improve extraction yields. These methods preserve the structural integrity and bioactivity of the compounds, making them highly suitable for further development. Additionally, modern analytical tools, such as high-performance liquid chromatography, mass spectrometry and metabolomic profiling, provide precise chemical characterization and quantification of the phytochemicals. The combination of advanced extraction techniques with chemical and metabolomic profiling ensures the high purity, efficacy and safety of phytomolecule-based insect-control agents. This review presents a novel extract-to-characterize framework integrating green extraction and metabolomic profiling to enhance phytochemical recovery and scalability of plant-based biopesticides.